Contributions of Neuroimaging to Understanding Language Deficits in Acute Stroke - Sebastian, Rajani; Breining, Bonnie L. (Seminars in Speech and Language, 2018)
Advances in structural and functional imaging techniques have provided new insights into our understanding of brain and language relationships. In this article, we review the various structural and functional imaging methods currently used to study language deficits in acute stroke. We also discuss the advantages and the limitations of each imaging modality and the applications of each modality in the clinical and research settings in the study of language deficits.
Keywords: DWI; PWI; DTI; fMRI; stroke; aphasia